Vestibular Syndromes in Childhood and Adolescence - Duarte, Juliana Antoniolli; Leão, Elisa Morais; Fragano, Daniel Sobral; Marquez, Germana Jardim; Pires, Anna Paula Batista de Ávila; Silva, Maria Laura Solferini; Ganança, Fernando Freitas (International Archives of Otorhinolaryngology, 2020)
Introduction The prevalence of vestibular disorders in childhood ranges from 0.4% to 15%; they may be the result of several factors, but most of the time it's an episodic vestibular syndrome related to migraine equivalents.Objective To evaluate the diagnostic and therapeutic aspects of children with vestibular signs and symptoms.Methods The present cross-sectional study evaluated data from the records of patients treated in an outpatient pediatric neurotology clinic over a 10-year period. These data included sociodemographic and clinical variables, results of complementary examinations, the treatment provided, and the clinical evolution.Results The sample was composed of 117 patients, with 54.7% of female subjects with a mean age of 10 years. The most prevalent diagnosis was benign paroxysmal vertigo of childhood (BPVC) (41.9%), followed by vestibular migraine (16.2%). The most prevalent complaint was vertigo (53.9% of the cases). Most patients (66.7%) had inadequate eating habits. Improvement of symptoms was observed in 40.4% of the patients treated with dietary guidance alone. In 80% of the cases, dietary counseling in combination with vestibular rehabilitation therapy achieved therapeutic success without the need of a drug treatment.Conclusion The predominant diagnosis was of BPVC, and its close relationship with the personal and family history of migraine, its benign evolution, and the importance of dietary guidance and vestibular rehabilitation for therapeutic success were observed.
Keywords: child; vertigo; migraine disorders; dizziness